A Quiver Full of Arrows - Archer, Jeffrey (London HarperCollins Publishers, 1980)
Two friends fall under the spell of a New York beauty, with unexpected results. An offhand remark is taken seriously by a Chinese sculptor, and a British diplomat becomes the owner of a priceless work of art. These are among the stories in this Jeffrey Archer collection.
English Fiction.
Keywords: Short stories -- Short stories, English -- Man-woman relationships